Estimating sustainable location for harvesting solar power using geographical information systems and remote sensing methods. Issue 1 (2nd January 2020) - Gupta, Yash; Sharma, Manoj
Abstract: In the last few decades, Renewable energy has received remarkable attention. This is partially because fossil fuels are depleting and the necessity for energy is rising because of the increasing population of the world. Among renewable sources of energy, solar energy is one such type that is becoming increasingly popular because it is inexhaustible, clean, and reliable. Solar radiation is obtained as heat and light that can be converted by solar thermal power generation into valuable thermal energy or electricity generation. With regard to efficiency and financial viability, the availability of trusted data on solar radiation is crucial to forecast the performance of solar power plants at different places in the country. This paper describes a general integrated structure for assessing land suitability for ideal positioning of photovoltaic solar energy panels based on a variety of geographic information system (GIS), remote sensing methods. The Location Viability Assessment, i.e. the areas appropriate for harvesting Solar Energy, is measured based on Global, Diffuse, Direct Solar Radiation Data that estimates the potential of the Solar Power Generation sites. Two interrelated steps were implemented in this study. First, Remote Sensing was used, including LANDSAT 8 satellite data, to extract the study area's land use/land cover map. Second, the Digital Elevation Model (DEM) was used to model the research zone map of aspect angles and slope maps. These results indicate the potential sites for Solar Power Generation.